Digital Literacy Students Facing to Independent Learning Independent Campus Curriculum - Halimatus Sakdiah; Maryam Jamilah (Community Medicine and Education Journal, 2022)
Digital literacy is a basic knowledge that is supported by interconnected information technology. This study aims to determine the digital literacy skills of students to face the Merdeka Learning Independent Campus (MBKM) curriculum. This research uses a descriptive method. The population of this research is students of Malikussaleh University and Al-Muslim University, Aceh. The research sample was conducted by purposive sampling technique. Data retrieval is done using Google forms. A total of 385 students filled out questionnaires distributed via a google form. Most of the research respondents were women (64%). Students' digital literacy is in the high category with an average of 67.5%. With an average student response of 80.4%, it shows the very high enthusiasm of students in implementing the MBKM curriculum.